Dual-frequency ultrasonic-assisted enzymolysis for synthesis of microstructure regulated biomass-derived porous carbon for high-performance supercapacitors - Zhaocai Teng; Kuihua Han; Meimei Wang; Jianhui Qi; Jiangwei Liu; Yingjie Li (Ultrasonics Sonochemistry)
Biomass-derived porous carbon (PC) has emerged as a promising candidate for electrode materials in energy storage applications, effective pretreatment of the precursor is a key strategy for enhancing the electrochemical performance of PC. However, challenges remain in achieving this goal through environmentally friendly, simple, and efficient methods. In this paper, a dual-frequency ultrasonic-assisted enzymolysis strategy combined with carbonization-activation method was proposed to prepare high-performance garlic peel-derived PC (DUGPC) for supercapacitors. Gentle and effective sonobiocatalysis facilitates microstructural regulation and composition management of the precursor, granting DUGPC an impressive specific surface area (SSA, 3006 m2/g), improved pore distribution, low metal impurity content (less than 100 ppm) and high wettability. As anticipated, DUGPC demonstrates excellent specific capacitance (408.77 F/g at 1 A/g) and rate performance (retention is 81.8 % at 50 A/g) surpassing most recently reported biomass-based PCs. In addition, the assembled aqueous symmetric supercapacitor achieves an excellent energy density of 15.78 Wh kg−1 at a power density of 50.04 W kg−1 with a remarkable cycle stability of 95.5 % after 10,000 cycles at 5 A/g, and the assembled 2.8 V high-voltage organic supercapacitor even exhibits an ultra-high energy density of 58.96 Wh kg−1 at a power density of 139.86 W kg−1. Significantly, this dual-frequency ultrasonic-assisted enzymolysis strategy is expected to be applicable to various biomass wastes and promotes the high-value utilization of biomass in the field of energy storage.